2006
DOI: 10.1007/s10886-006-9185-x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile Hormone III Influences Task-Specific Cuticular Hydrocarbon Profile Changes in the Ant Myrmicaria eumenoides

Abstract: We investigated the influence of juvenile hormones (JH) on the composition of cuticular hydrocarbons (CHCs) and the division of labor in colonies of the African ant Myrmicaria eumenoides. CHCs have long been implicated in nestmate recognition in social insect colonies. In M. eumenoides, the CHC profiles also vary with the task performed from brood-tender-type to forager type. The endocrine factors regulating the task allocation as well as the intracolonial recognition cues are not well understood, but JHs are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 65 publications
2
26
0
Order By: Relevance
“…The effects of JH observed on leaf-cutting ants have remarkable similarities with those seen in the best-studied social insect, the honey bee Apis mellifera, in which experimentally elevated JH levels lead to precocious foraging (Sullivan et al, 2000), possibly due to the same behavioural mechanisms as we show here in leafcutting ants. The results also fit with a number of correlational studies in which JH levels have been found to be higher in foragers of several different ant species, as well as wasps, bees and termites (Dolezal et al, 2009;Giray et al, 2005;Lengyel et al, 2007;Penick et al, 2011). This suggests that JH may have a highly conserved role as a key endocrine mediator of division of labour within eusocial insect societies that has been key to their ecological and evolutionary success.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The effects of JH observed on leaf-cutting ants have remarkable similarities with those seen in the best-studied social insect, the honey bee Apis mellifera, in which experimentally elevated JH levels lead to precocious foraging (Sullivan et al, 2000), possibly due to the same behavioural mechanisms as we show here in leafcutting ants. The results also fit with a number of correlational studies in which JH levels have been found to be higher in foragers of several different ant species, as well as wasps, bees and termites (Dolezal et al, 2009;Giray et al, 2005;Lengyel et al, 2007;Penick et al, 2011). This suggests that JH may have a highly conserved role as a key endocrine mediator of division of labour within eusocial insect societies that has been key to their ecological and evolutionary success.…”
Section: Resultssupporting
confidence: 85%
“…The physiological effect of diet on morphological caste determination in honey bees is mediated by juvenile hormone (JH) levels, with JH also mediating the age polyethism and behavioural task propensity of adult workers (Amsalem and Malka, 2014;Schulz et al, 2002;Sullivan et al, 2000). JH has wide-ranging effects in insects (Flatt et al, 2005;Hartfelder, 2000;Nijhout and Wheeler, 1982;Sullivan et al, 2000), and a number of correlational studies have found JH levels to be higher in foragers compared with in-nest workers for several ant, bee and wasp species (Dolezal et al, 2012;Giray et al, 2005;Lengyel et al, 2007;Penick et al, 2011;Shorter and Tibbetts, 2009), suggesting that JH may have a general regulatory function in the division of labour in insect societies. However, it is unclear what behavioural changes produce this agerelated switch, and direct experimental evidence for the influence of JH outside of the honey bee model system is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…queen), but if she disappears, former workers fighting to inherit the nest show increased JH levels . Finally, as in other hymenopteran societies (O'Donnell and Jeanne, 1993;Robinson and Vargo, 1997;Lengyel et al, 2007;Penick et al, 2011;Dolezal et al, 2012), JH appears to modulate age-related changes in worker activity, a function that is condition and context dependent in adults of Polistes (West-Eberhard, 1996;Giray et al, 2005;Shorter and Tibbetts, 2009). …”
Section: Introductionmentioning
confidence: 78%
“…Th e cuticular compounds may also play a role in caste regulation similar to primer pheromones LeConte & Hefetz 2008). Th erefore, the chemical signature and its variations depend on a wide range of factors: endog-enous factors, such as endocrine or enzymatic factors and the regulation of transport paths, etc (Lengyel et al 2007;Schal et al 2003;Fan et al 2004), as well as exogenous factors, such as climate and season (Bagnères et al 1990), diet (Liang and Silverman 2000), the presence of predators, etc. Th e predominance of these factors varies between insects (VanderMeer & Morel 1998).…”
mentioning
confidence: 99%
“…It has been shown that JH-III can induce diff erentiation into soldiers, partly by changes in the expression of the coding genes, for example for the muscular proteins of the mandibles (Hrdy & Krecek 1972;Park & Raina 2004;Scharf et al 2003). Other studies have shown that this hormone regulates the synthesis and possibly the transport of CHCs in Myrmicaria eumenoides ants (Lengyel et al 2007). In this study, the experiment to induce workers into soldiers by ingesting JH did not succeed in forming pre-soldiers in 35 days.…”
mentioning
confidence: 99%